2017
DOI: 10.2196/publichealth.7933
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings of a Technology-Delivered Sexual Health Promotion Program for Black Men Who Have Sex With Men: Quasi-Experimental Outcome Study

Abstract: BackgroundHuman immunodeficiency virus (HIV) disproportionately affects black men who have sex with men (MSM), yet there are few evidence-based interventions specifically designed for black MSM communities. In response, the authors created Real Talk, a technology-delivered, sexual health program for black MSM.ObjectiveThe objective of our study was to determine whether Real Talk positively affected risk reduction intentions, disclosure practices, condom use, and overall risk reduction sexual practices.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
(53 reference statements)
2
14
0
1
Order By: Relevance
“…None of significant differences were found between both intervention and control groups in terms of sexual risk behaviours. However, the authors reported a higher likelihood of intention in using condom and motivating HIV testing in the intervention group than that in the control group [87].…”
Section: Computer-assisted Intervention (N = 3)mentioning
confidence: 79%
See 2 more Smart Citations
“…None of significant differences were found between both intervention and control groups in terms of sexual risk behaviours. However, the authors reported a higher likelihood of intention in using condom and motivating HIV testing in the intervention group than that in the control group [87].…”
Section: Computer-assisted Intervention (N = 3)mentioning
confidence: 79%
“…Sexual risk behaviors were the most common primary outcomes (n = 32 studies), following by HIV/STI testing and self-testing (n = 18 studies) and HIV/STI disclosure, stigma, self-esteem, and internalized homonegativity (n = 9 studies). Several studies focused on HIV/STI prevention knowledge and attitudes [47,56,67,86,87], HIV disclosure [60,62,79,[87][88][89], gonorrhea and chlamydial infection and treatment [90], or pre-exposure prophylaxis uptake [57,91] and adherence [92,93]. Reback et al (2012) had an additional outcome regarding the frequency of methamphetamine use among MSM [50], and Hightow-Weidman et al (2019) investigated the intention to use a condom, attitudes toward safe sexual behaviours, condom use self-efficacy, depressive symptoms, social support and social isolation [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma-focused interventions have generally been delivered in-person; while demonstrating efficacy, these interventions have been implemented on a relatively small scale (177). HIV prevention interventions that include Black MSM have included stigma as an intervention topic (178)(179)(180) and a growing number of eHealth interventions have been developed for Black MSM (178,181,182) but few interventions have addressed intersectional stigma (169,183). To date, there are few effective interventions for cis-gender, gay or bisexual FB Black Caribbean immigrant men to promote HIV testing (18).…”
Section: Approaches To Reduce Stigma Of Hiv Testingmentioning
confidence: 99%
“…HIV prevention interventions that include Black MSM have included stigma as an intervention topic (178)(179)(180) and a growing number of eHealth interventions have been developed for Black MSM (178,181,182), but few interventions have addressed intersectional stigma (169,183). Stigma-focused interventions have generally been delivered in-person and have been implemented on a relatively small scale (177).…”
Section: Community-level Campaignsmentioning
confidence: 99%